Driving Pressure, Elastance, and Outcomes in a Real-World Setting: A Bi-Center Analysis of Electronic Health Record Data. (24th February 2023) - Goodwin, Andrew J.; Brinton, Daniel L.; Terry, Charles; Carter, George; Files, D. Clark; Kirchoff, Katie; Ford, Dee W.; Simpson, Annie N.
Abstract : OBJECTIVES: Emerging evidence suggests the potential importance of inspiratory driving pressure (DP) and respiratory system elastance (ERS ) on outcomes among patients with the acute respiratory distress syndrome. Their association with outcomes among heterogeneous populations outside of a controlled clinical trial is underexplored. We used electronic health record (EHR) data to characterize the associations of DP and ERS with clinical outcomes in a real-world heterogenous population. DESIGN: Observational cohort study. SETTING: Fourteen ICUs in two quaternary academic medical centers. PATIENTS: Adult patients who received mechanical ventilation for more than 48 hours and less than 30 days. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: EHR data from 4, 233 ventilated patients from 2016 to 2018 were extracted, harmonized, and merged. A minority of the analytic cohort (37%) experienced a Pao 2 /Fio 2 of less than 300. A time-weighted mean exposure was calculated for ventilatory variables including tidal volume (VT ), plateau pressures (PPLAT ), DP, and ERS . Lung-protective ventilation adherence was high (94% with VT < 8.5 mL/kg, time-weighted mean VT = 6. 8 mL/kg, 88% with PPLAT ≤ 30 cm H2 O). Although time-weighted mean DP (12.2 cm H2 O) and ERS (1.9 cm H2 O/[mL/kg]) were modest, 29% and 39% of the cohort experienced a DP greater than 15 cm H2 O or an ERS greater than 2 cm H2 O/(mL/kg), respectively. Regression modeling with adjustment for relevant covariates determined that exposure to time-weighted mean DP (> 15 cm H2 O) was associated with increased adjusted risk of mortality and reduced adjusted ventilator-free days independent of adherence to lung-protective ventilation. Similarly, exposure to time-weighted mean ERS greater than 2 cm H2 O/(mL/kg) was associated with increased adjusted risk of mortality. CONCLUSIONS: Elevated DP and ERS are associated with increased risk of mortality among ventilated patients independent of severity of illness or oxygenation impairment. EHR data can enable assessment of time-weighted ventilator variables and their association with clinical outcomes in a multicenter real-world setting.